Response of Growth, Yield and Yield Components of two Sunflower Varieties (Helianthus annuus L.) to Nitrogen Fertilization - Saeed, Rostam K.; Berdawood, Karzan A. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper, we focus on obtaining an approximate solution of the two types of two- dimensional linear Volterra-Fredhom integral equations of the second kind. Series solution method is reformulated and applied with different bases functions for finding an approximate solution (sometimes the exact solution) for the above two types of integral equations. This is done by computer program with the aid of the Maple code program version 13 for all the above prescribed methods. Furthermore, we proved some theoretical results on the convergence analysis of the presented methods
Keywords: VolterraFredhom integral equations; Power Series; Orthogonal Functions